2014
DOI: 10.1016/j.jcrs.2013.08.055
|View full text |Cite
|
Sign up to set email alerts
|

Opaque bubble layer: Incidence, risk factors, and clinical relevance

Abstract: Thicker corneas tended to develop an OBL during femtosecond laser-assisted LASIK surgery. An OBL did not affect postoperative visual acuity except for a mild decrease in scotopic contrast sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 12 publications
1
24
1
Order By: Relevance
“…Our results confirm the correlations between CCT and OBL shown in previous studies 12,14 with a larger population of 198 eyes: thicker corneas were associated with more frequent and larger OBL.…”
Section: Discussionsupporting
confidence: 92%
“…Our results confirm the correlations between CCT and OBL shown in previous studies 12,14 with a larger population of 198 eyes: thicker corneas were associated with more frequent and larger OBL.…”
Section: Discussionsupporting
confidence: 92%
“…[ 7 20 ] In addition, although generally safe, several complications may still occur during or after LASIK, including flap-related complications such as opaque bubble layer, flap buttonholes, free flaps or incomplete flaps, as well as diffuse lamellar keratitis, flap striae, flap displacement, epithelial ingrowth, and stromal wrinkles. [ 34 35 36 ] Once happened, the visual prognosis may possibly be affected. Therefore, regarding safety issue, PRK represents a more reasonable choice relative to LASIK for correcting the residual refractive error, for avoiding the aforementioned complications,[ 7 15 ] especially in this patient population with higher demand on vision and lower tolerance to risks.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Zhao et al [5] recommended to not use the CCL technique in the presence of an opaque bubble layer (OBL), uneven laser scanning, or in any other situation that may increase the difficulty of lenticule extraction. Although there have been no studies on the incidence of OBL formation during SMILE surgeries, Liu et al [10] reported an OBL rate of 52.5 % during femtosecond laser-assisted in situ keratomileusis (LASIK) procedures, which represents a considerable effect.…”
Section: Discussionmentioning
confidence: 99%